2017
DOI: 10.1002/2016jc012513
|View full text |Cite
|
Sign up to set email alerts
|

A simulation of small to giant Antarctic iceberg evolution: Differential impact on climatology estimates

Abstract: We present a simulation of Antarctic iceberg drift and melting that includes small, medium‐sized, and giant tabular icebergs with a realistic size distribution. For the first time, an iceberg model is initialized with a set of nearly 7000 observed iceberg positions and sizes around Antarctica. The study highlights the necessity to account for larger and giant icebergs in order to obtain accurate melt climatologies. We simulate drift and lateral melt using iceberg‐draft averaged ocean currents, temperature, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(129 citation statements)
references
References 43 publications
(160 reference statements)
5
88
0
Order By: Relevance
“…This layer could be hundreds of meters below mean-global sea level if a large iceberg was positioned above it. This means that there is no need to manually embed icebergs into the ocean by integrating ocean fields over the icebergs' thickness, as suggested in Merino et al [2016], or to integrate ocean fields over an implied iceberg surface area, as suggested in Rackow et al [2017]. Within the iceberg model, the ocean model fields are interpolated onto the Lagrangian grid using a bilinear interpolation scheme.…”
Section: Ice-ocean Couplingmentioning
confidence: 99%
See 4 more Smart Citations
“…This layer could be hundreds of meters below mean-global sea level if a large iceberg was positioned above it. This means that there is no need to manually embed icebergs into the ocean by integrating ocean fields over the icebergs' thickness, as suggested in Merino et al [2016], or to integrate ocean fields over an implied iceberg surface area, as suggested in Rackow et al [2017]. Within the iceberg model, the ocean model fields are interpolated onto the Lagrangian grid using a bilinear interpolation scheme.…”
Section: Ice-ocean Couplingmentioning
confidence: 99%
“…For an element in the interior of a large structure, the distance from the edge of the structure is large, and so using M b for the basal melt is not appropriate. Instead, the basal melt M s is determined using the three equation model for basal melt, which is a typical melting parametrization used beneath ice shelves [Holland and Jenkins, 1999], and has been used to parametrize melt rates beneath large icebergs in previous studies [Silva et al, 2006;Rackow et al, 2017].…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2017msmentioning
confidence: 99%
See 3 more Smart Citations